Preparation method of antibacterial metal porous implant based on powder laying type laser printing technology

The preparation of antibacterial metal porous implants through powder-laying laser printing technology, which solved the problem of mismatch between the elastic modulus of titanium alloy implants and bones and lack of antibacterial function, and achieved the mechanical compatibility and durable antibacterial of the implants. Effect.

CN119187573APending Publication Date: 2024-12-27GUILIN UNIV OF ELECTRONIC TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411297041.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing titanium alloy medical implants have loose bond interfaces and stress shading effects due to the mismatch between the block structure and the elastic modulus of bones, and the lack of antibacterial function, which limits its application in medicine.

Method used

Antibacterial metal porous implants are prepared by powder-paving laser printing technology. Through three-dimensional Voronoi polyhedral structure design and nano-scale Cu particle doping, the porous structure and antibacterial properties of the material are achieved, avoiding stress masking effects and providing long-lasting bactericidal function.

Benefits of technology

The elastic modulus matching between the implant and the bone is achieved, which promotes the growth of new tissues and bone formation, and has efficient and broad-spectrum antibacterial properties, simplifies the preparation process and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119187573A_ABST
    Figure CN119187573A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an antibacterial metal porous implant based on a powder laying type laser printing technology, and belongs to the technical field of metal additive manufacturing. The method comprises the following steps: firstly, designing a porous structure of a bone trabecula on the basis of a three-dimensional Voronoi diagram algorithm; then, a vacuum ball milling technology is adopted for obtaining Cu particle doped titanium alloy mixed powder with nanoscale Cu particles distributed in a dispersed mode; then, the bone trabecula structure Cu-doped antibacterial titanium alloy porous implant is prepared by adopting a powder laying type laser printing technology; and finally, testing the antibacterial performance and the compression performance of the titanium alloy porous implant. The titanium alloy porous implant with the bone trabecula structure obtained through laser powder laying type additive manufacturing not only has good biological and mechanical property matching, but also effectively avoids the stress shielding effect between a traditional blocky implant and a human skeleton, and is suitable for manufacturing various biomedical implants such as lumbar vertebra bones, tubular bones and mandible bones.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field The present invention relates to the technical field of metal additive manufacturing, and in particular to a method for preparing an antibacterial porous metal implant and the antibacterial porous metal implant. Background Art Medical titanium alloys are widely used in orthopedics and dentistry due to their excellent biocompatibility, low elastic modulus, high specific strength and good corrosion resistance, such as bone needles, bone nails, bone plates, artificial joints, dental trays, dental implants, dental orthopedic wires and other biomedical products. However, at present, traditional manufacturing technologies are still mainly used in clinical practice to prepare titanium alloy medical implants, such as casting, sintering, powder metallurgy, etc. The mismatch in elastic modulus between block metal implants and human bones can easily lead to two problems during surgical implantation or postoperative recovery. One is the loosening of the bonding interface due to mechanical mismatch between the metal implant and the surrounding bone; the other is the stress shielding effect that easily leads to functional degradation of the implant or even implant failure. In addition, titanium alloys do not have bactericidal function due to their biological inertness. They cannot prevent infection problems caused during implantation, nor can they solve the problem of bone tissue integration after implantation. At present, antibacterial coatings can be prepared by surface modification (such as ion implantation, thermal spraying, magnetron sputtering, etc.) to give titanium alloys bactericidal function. However, these methods have certain limitations, such as complex coating preparation process, high cost, poor bonding between coating and substrate, and easy loss of long-lasting bactericidal function due to wear. The above shortcomings have greatly restricted the clinical application and development of titanium alloy antibacterial coatings. Summary of the invention In view of the problems existing in the existing block titanium alloy implants in the background technology, such as stress shielding effect and lack of antibacterial function, the present application provides a method for preparing an antibacterial metal porous implant based on powder-spreading laser printing technology. The metal porous implant designed by the present invention can not only achieve a matching design between its elastic modulus and its own bone elastic modulus, but also effectively avoid the stress shielding effect between the surrounding tissues, promote the growth of new tissues after surgery, and form an effective mesh with the host bone. In addition, during the printing process, antibacterial elements can be diffused in the print by means of particle doping, so that it has a high-efficiency, broad-spectrum and long-lasting bactericidal function. There are no research reports on this method so far. In a first aspect, an embodiment of the present invention provides a method for preparing an antibacterial porous metal implant, comprising the following steps: Step S1 randomly distributes N seed points in a given three-dimensional geometric design area; Step S2 uses a three-dimensional Voronoi diagram algorithm to divide the space into N Voronoi polyhedrons using the seed points generated in step S1; Step S3 extracts the edges of the polyhedron generated in step S2 and further generates solid rods to obtain a porous structure of trabecular bone, with a porosity of 50-90 vol.%, a pore size of 200-800 μm, and an average diameter of the solid rods of 200-400 μm; Step S4: using a microbalance to weigh nano-scale Cu particles and Ti6Al4V titanium alloy powder for additive manufacturing, respectively; the Cu mass fraction in the mixed powder is 0.5-10wt.%, the Cu particle size is 50-800nm, and the particle size range of the titanium alloy powder is 15-53μm; Step S5: The mixed powder obtained by weighing in step S4 is placed in a ball mill containing grinding balls for mixing and stirring. The grinding balls are made of corundum, the grinding ball particle size range is 2-5 mm, the ball milling speed is 250-400 rpm / min, the ball milling time is 2.5-5.5 h, and the ball mill is filled with 100% inert argon gas for protection. Step S6: filtering the mixed powder obtained by ball milling in step S5 through an ultrasonic vibration sieve and placing it in a vacuum drying oven for drying for printing, the mesh size of the sieve is 120 meshes, the ultrasonic vibration frequency is 25-40KHz, the drying oven is set at 150-200°C, and the protective atmosphere is 100% argon; Step S7: import the trabecular bone structure drawn in step S3 into the layered slicing software for horizontal layered slicing, with the spacing between adjacent layers being 25-35 μm; Step S8: import the sliced ​​file in step S7 into a powder-laying laser printing device in .stl format; Step S9: using an industrial dust collector to clean the printing chamber of the laser printing device and installing the titanium alloy metal substrate with a polished surface in the printing chamber, the positive and negative errors of the four corners of the substrate in the horizontal direction shall not exceed 20 μm; Step S10: Place the mixed powder dried and stored in step S6 into the powder chamber, evacuate the chamber, introduce argon gas, and heat the substrate. The oxygen content in the printing chamber is ≤300ppm, and the substrate preheating temperature is 100-200°C. Step S9 opens the .stl format file imported in step S8 and sets the printing parameters, laser power 150-350W, scanning speed 200-400mm / s, scanning spacing 0.08-0.1mm, and adjacent layer height 25-35μm; Step S10: Scan and print the laser layer by layer according to the parameters set in step S9, the laser scanning direction is the same within the same layer and the angle between adjacent layers is 67°; Step S11: After the printing work in step S10 is completed, the substrate is cooled to room temperature, the residual powder in the printing cavity and the powder cavity is cleaned, the substrate is removed, and the printed part is cut off from the surface of the substrate by wire cutting to obtain a Cu particle-doped antibacterial trabecular titanium alloy porous implant; Step S12: Place the experimental consumables for antibacterial performance test and the Cu-doped titanium alloy printed parts after alcohol ultrasonic cleaning in a high temperature and high pressure box for sterilization. The alcohol ultrasonic cleaning time is 20 minutes. The temperature and time of the sterilization treatment are 121°C and 20 minutes respectively. The reference standard for the antibacterial performance test is GB / T 2591. Step S13: After the sterilized printout in step S12 is placed in a 24-well plate, a bacterial suspension is dripped onto the surface of the printout to be observed using a pipette. The concentration and volume of the bacterial suspension are 3×10 5 ~4×10 5 CFU / mL and 100 μL; Step S14: After the printed sample in step S13 is taken out from the 24-well plate, it is placed in a centrifuge tube with PBS buffer added thereto for dilution, and mechanically shaken to remove the bacteria. The volume of the PBS buffer is 3 mL, and the mechanical shaking time is 2 min. Step S15: first use a pipette to take the diluted and shaken bacterial suspension and drop it onto a culture medium plate, then use a digital camera to take pictures and count, the volume of the bacterial suspension is 100 μL, and the colony counting method refers to the standard "GB4789.2-2016"; Step S16: grinding the upper surface of the upper cover and the lower surface of the lower cover of the porous implant prepared in step S11 with sandpaper with a particle size of 2000 mesh; Step S17: placing the porous implant that has been polished in step S16 on a universal testing machine for compression performance testing, with a compression rate of 0.5-1.5 mm / min. In a second aspect, an embodiment of the present invention provides an antibacterial porous metal implant, which is prepared by the method for preparing an antibacterial porous metal implant according to the first aspect. The antibacterial metal porous implant of the present invention is formed and manufactured by using powder-spreading laser printing technology in the preparation process. The antibacterial metal porous implant formed can meet the demanding production requirements of precise and complex porous structure design and personalized and small batches in the field of medical transplantation. Compared with the traditional process, the matching design between its elastic modulus and its own bone elastic modulus can be achieved through fine regulation of geometric structure parameters, effectively avoiding the stress shielding effect between the surrounding tissues, promoting the growth of new tissues after surgery and forming effective meshing with the host bone. Moreover, when the antibacterial metal porous implant material is formed by using powder-spreading laser printing technology in the preparation process, the mixed powder prepared by doping nano-scale Cu metal powder with antibacterial efficacy in the special printing titanium alloy powder is used for additive manufacturing, so as to ensure the diffuse distribution of antibacterial Cu atoms in the antibacterial metal porous implant of the present invention, and avoid the poor bonding between the antibacterial coating and the substrate prepared by traditional surface modification means, and the loss of long-lasting bactericidal function due to wear. This antibacterial porous metal implant not only simplifies the traditional preparation process and saves raw materials and manufacturing costs, but also ensures long-lasting and stable antibacterial efficacy and avoids stress shielding effects. BRIEF DESCRIPTION OF THE DRAWINGS In order to describe the technical solution of the embodiment of the invention in more detail, the following briefly introduces the drawings used in the description of the embodiment. Obviously, the drawings described below are only drawings of some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on such drawings without creative work. Figure 1 is a flow chart of a method for preparing an antibacterial porous metal implant according to one embodiment of the present invention; Figure 2 The geometric structure of the porous trabecular implant designed in step S3 of one of the technical solutions of the present invention; Figure 3 It is a schematic diagram of the laser scanning strategy for preparing the antibacterial porous metal implant in step S6 of the third technical solution of the present invention; Figure 4 It is an X-ray tomographic image of the antibacterial porous metal implant prepared by using the powder-laying laser printing technology in step S7 of the third technical solution of the present invention; Figure 5 This is the antibacterial performance test result of the antibacterial porous metal implant prepared by powder-laying laser printing technology in step S5 of the fourth technical solution of the present invention. DETAILED DESCRIPTION

[0033] It should be noted that the specific technical solutions described are only part of the technical solutions of this application, not all of the technical solutions. Based on the technical solutions in this application, all other technical solutions obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0034] One of the technical solutions of the present invention is to design a porous implant with a trabecular structure, comprising the following steps:

[0035] Step S1: randomly distribute N seed points in a given three-dimensional geometric design area;

[0036] Step S2: using a three-dimensional Voronoi diagram algorithm based on the seed point set to divide the space into N Voronoi polyhedrons;

[0037] Step S3: extracting the edges of each polyhedron to generate solid rods can generate a random porous grid solid structure.

[0038] Preferably, the porosity of the porous grid entity structure in step S3 is 50-90 vol.%;

[0039] Preferably, the pore size of the porous grid entity structure described in step S3 is 200-800 μm;

[0040] Preferably, the average diameter of the solid rods of the porous grid solid structure described in step S3 is 200-400 μm.

[0041] The second technical solution of the present invention is to prepare a Cu particle doped titanium alloy mixed powder, comprising the following steps:

[0042] Step S1: weighing nano-scale Cu particles using a microbalance;

[0043] Step S2: using a microbalance to weigh Ti6Al4V titanium alloy powder for additive manufacturing;

[0044] Step S3: placing the weighed Cu particles and titanium alloy powder into a ball mill containing grinding balls;

[0045] Step S4: setting equipment parameters to mix and stir the Cu particles doped titanium alloy mixed powder;

[0046] Step S5: using an ultrasonic vibration screen to screen the Cu particle-doped titanium alloy mixed powder after ball milling;

[0047] Step S6: placing the screened Cu particles-doped titanium alloy mixed powder into a vacuum drying oven for drying.

[0048] Preferably, the mass fraction of Cu particles in the mixed powder described in step S1 is 0.5-10wt.%, and the remainder is Ti6Al4V titanium alloy printing powder;

[0049] Preferably, the nano-scale Cu particles described in step S1 have a size of 50-800 nm;

[0050] Preferably, the particle size of the titanium alloy powder in step S2 is in the range of 15-53 μm;

[0051] Preferably, 10% of the particles in the titanium alloy powder described in step S2 have a particle size of ≤19.3 μm;

[0052] Preferably, 50% of the particles in the titanium alloy powder described in step S2 have a particle size of ≤34.5 μm;

[0053] Preferably, 90% of the particles in the titanium alloy powder described in step S2 have a particle size of ≤53.7 μm;

[0054] Preferably, the bulk density of the titanium alloy powder in step S2 is 2.37 g / cm 3 ;

[0055] Preferably, the fluidity of the titanium alloy powder in step S2 is 42s / 50g;

[0056] Preferably, the grinding ball material in step S3 is corundum;

[0057] Preferably, the grinding ball particle size range of step S3 is 2-5 mm;

[0058] Preferably, the ball milling speed of the ball mill in step S4 is set to 250-400 rpm / min;

[0059] Preferably, the ball milling time of the ball mill described in step S4 is set to 2.5-5.5h;

[0060] Preferably, the working atmosphere of the ball mill in step S4 is 100% argon protection;

[0061] Preferably, the mesh size of the sieve in step S5 is 120 meshes;

[0062] Preferably, the ultrasonic vibration frequency in step S5 is 25-40KHz;

[0063] Preferably, the setting temperature of the drying oven in step S6 is 150-200°C;

[0064] Preferably, the protective atmosphere of the drying oven in step S6 is 100% argon.

[0065] The third technical solution of the present invention is to print a porous titanium alloy implant with a trabecular structure by laser powder additive manufacturing, comprising the following steps:

[0066] Step S1: importing the porous structure of trabecular bone into the layered slicing software for horizontal layered slicing;

[0067] Step S2: Import the sliced ​​file into the powder laser printing device in .stl format;

[0068] Step S3: using an industrial dust collector to clean the printing chamber and installing a titanium alloy printing substrate with a surface that has been ground and polished;

[0069] Step S4: loading the Cu particles doped titanium alloy mixed powder into the powder chamber of the printing device, evacuating the chamber, introducing argon gas and heating the substrate;

[0070] Step S5: Setting main process parameters in the metal printing equipment operation interface;

[0071] Step S6: The laser scans the metal powder bed layer by layer according to the planned path to melt and solidify the metal powder bed;

[0072] Step S7: After the printing is completed and the printing chamber is cooled to room temperature, the residual powder in the equipment is cleaned, the substrate is removed, and the printed part is cut from the surface of the substrate by wire cutting to obtain a Cu particle-doped antibacterial trabecular titanium alloy porous implant.

[0073] Preferably, the spacing between adjacent slices in the horizontal slicing described in step S2 is 25-35 μm;

[0074] Preferably, the positive and negative value errors in the horizontal direction of the four corners of the substrate after installation in step S3 do not exceed 20 μm;

[0075] Preferably, the oxygen content of the printing chamber after vacuuming in step S4 is ≤300ppm;

[0076] Preferably, the substrate preheating temperature in step S4 is 100-200° C.;

[0077] Preferably, the laser power in step S5 is 150-350W;

[0078] Preferably, the scanning speed in step S5 is 200-400 mm / s;

[0079] Preferably, the scanning interval in step S5 is 0.08-0.1 mm;

[0080] Preferably, the height between adjacent layers in step S5 is 25-35 μm;

[0081] Preferably, the laser scanning directions in the same layer in step S6 are the same;

[0082] Preferably, the angle between the laser scanning directions in adjacent layers in step S6 is 67°.

[0083] The fourth technical solution of the present invention: referring to the national standard "GB / T 2591" and using Staphylococcus aureus ATCC25923 to test the antibacterial properties of the SLM titanium alloy porous implant, comprising the following steps:

[0084] Step S1: Place the experimental consumables and the Cu-doped titanium alloy printed parts after alcohol ultrasonic cleaning into a high temperature and high pressure box for sterilization;

[0085] Step S2: After the printout is placed in a 24-well plate, a bacterial suspension is dripped onto the surface of the printout to be observed using a pipette;

[0086] Step S3: placing the printed piece with the bacterial suspension added thereto in a constant temperature and humidity incubator for incubation;

[0087] Step S4: After the printed sample is taken out from the 24-well plate, it is placed in a centrifuge tube with PBS buffer added for dilution, and mechanically shaken to remove the bacteria;

[0088] Step S5: first use a pipette to take the diluted and shaken bacterial suspension and drop it onto a culture medium plate, and then use a digital camera to take pictures and count;

[0089] Preferably, the alcohol ultrasonic cleaning time in step S1 is 20 minutes;

[0090] Preferably, the temperature of the sterilization treatment in step S1 is 121°C;

[0091] Preferably, the sterilization treatment time in step S1 is 20 minutes;

[0092] Preferably, the concentration of the bacterial suspension in step S2 is 3×10 5 ~4×10 5 CFU / mL;

[0093] Preferably, the volume of the bacterial suspension in step S2 is 100 μL;

[0094] Preferably, the temperature of the constant temperature and humidity incubator described in step S3 is set to 37° C.

[0095] Preferably, the humidity of the constant temperature and humidity incubator described in step S3 is set to 90%;

[0096] Preferably, the culture time in step S3 is 24h;

[0097] Preferably, the volume of the PBS buffer in step S4 is 3 mL;

[0098] Preferably, the mechanical oscillation time in step S4 is 2 minutes;

[0099] Preferably, the volume of the bacterial suspension in step S5 is 100 μL;

[0100] Preferably, the reference standard of the colony counting method described in step S5 is GB 4789.2-2016;

[0101] The antibacterial performance test results of the Cu-doped titanium alloy printed parts prepared in this example are as follows: Figure 4 As shown in the figure, it can be seen that the SLM-type additively manufactured trabecular titanium alloy porous implant prepared by the present invention has excellent antibacterial properties.

[0102] Technical solution 5 of the present invention: Testing the compression performance of the SLM titanium alloy porous implant comprises the following steps:

[0103] Step S1: grinding the upper surface and the lower surface of the porous implant using metallographic sandpaper;

[0104] Step S2: using a universal testing machine to perform a compression performance test on the porous implant;

[0105] Preferably, the particle size of the metallographic sandpaper in step S1 is 2000 mesh;

[0106] Preferably, the compression speed in step S2 is 0.5-1.5 mm / min;

[0107] The compression performance of the Cu-doped titanium alloy porous implant with trabecular structure prepared in this embodiment was tested and found to be: elastic modulus 5.7 GPa, maximum compressive strength 60 MPa, material strength and elastic modulus performance are appropriate, meeting the mechanical compatibility requirements of the implant.

[0108] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. A method for preparing an antibacterial porous metal implant based on powder-spreading laser printing technology, characterized in that: The following steps are involved: (1) Trabecular porous structure design: Design of trabecular porous implants based on the three-dimensional Voronoi diagram algorithm; (2) Preparation of Cu particle-doped titanium alloy mixed powder: Nano-scale Cu particles and printing-specific titanium alloy powder are mixed and stirred using vacuum ball milling technology, and the ball-milled powder is filtered using an ultrasonic vibration screen to remove impurities and stored in a vacuum drying oven for printing. In the mixed powder, the mass fraction of Cu particles is 0.5-10wt.%, and the remainder is titanium alloy printing powder; (3) Laser powder-laying additive manufacturing: Nano-scale Cu particles doped with titanium alloy mixed powder are placed in the powder cavity of the printing device. The laser scans the metal powder bed layer by layer according to the planned path. The powder quickly melts and solidifies to achieve a metallurgical bonding effect, and finally obtains the trabecular structure Cu-doped antibacterial titanium alloy porous implant designed by the model; (4) Antibacterial performance test: The antibacterial performance of Cu-doped titanium alloy porous implants was tested using Staphylococcus aureus ATCC25923 in accordance with the national standard GB / T 2591. The colony counting method was based on the standard GB 4789.2-2016. (5) Compression performance test: A universal testing machine was used to test the compression performance of the trabecular structure Cu-doped antibacterial titanium alloy porous implant, and the test data was extracted to obtain data such as elastic modulus and maximum compression strength.

2. The method according to claim 1, characterized in that The metal powder capable of providing antibacterial properties includes at least one of Cu, Ag or Zn.

3. The method according to claim 1, characterized in that The medical metal material that can be applied to the field of human bone implantation includes at least one of cobalt-based alloys, titanium-based alloys, stainless steel, shape memory alloys, precious metals, pure metal niobium, zirconium, titanium or tantalum.

4. The method for designing a porous implant with a trabecular structure according to step (1) of claim 1, characterized in that: The porosity of the trabecular porous area is 50-90 vol.%; Preferably, the pore size of the trabecular porous region is 200-800 μm; Preferably, the average diameter of the solid rods in the porous region of the trabeculae is 200-400 μm.

5. The method for preparing the Cu particle-doped titanium alloy mixed powder according to step (2) of claim 1, characterized in that: The size of the nano-scale Cu particles is 50-800nm.

6. The method for preparing the Cu particle-doped titanium alloy mixed powder according to step (2) of claim 1, characterized in that: The particle size range of the titanium alloy printing powder is 15-53 μm.

7. The method for preparing the Cu particle-doped titanium alloy mixed powder according to step (2) of claim 1, characterized in that: The parameters of the ball milling equipment are ball milling speed 250-400rpm / min, ball milling time 2.5-5.5h, and working atmosphere 100% argon; Preferably, the grinding balls of the ball mill are corundum balls with a particle size range of 2-5 mm.

8. The laser powder additive manufacturing method according to step (3) of claim 1, characterized in that: The printing parameters of the additive manufacturing equipment are substrate preheating temperature 100-200°C, laser power 150-350W, scanning speed 200-400mm / s, scanning spacing 0.08-0.1mm, and adjacent layer height 25-35μm; preferably, the laser scanning direction angle in adjacent layers is 67 。 .

9. The method for testing the antibacterial properties according to step (4) of claim 1, characterized in that: The test method described refers to the national standard "GB / T 2591".

10. The method for testing the antibacterial properties according to step (4) of claim 1, characterized in that: The bacterial colony is Staphylococcus aureus ATCC25923.

11. The method for testing the antibacterial properties according to step (4) of claim 1, characterized in that: The colony counting method described herein refers to the national standard "GB 4789.2-2016".

12. The method for compression performance testing according to step (5) of claim 1, characterized in that: The compression rate of the universal testing machine is 0.5-1.5 mm / min.